2014
DOI: 10.1097/ta.0000000000000266
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, multi-institutional study of pediatric all-terrain vehicle crashes

Abstract: Epidemiologic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 21 publications
4
31
0
Order By: Relevance
“…Recent studies illustrate the ongoing and serious nature of ATV crashes. 10,11,15 One report showed that pediatric ATV-related traumas were associated with more interhospital transfers and higher injury severity scores than other trauma admissions. 15 …”
Section: Discussion Pediatric Fatalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies illustrate the ongoing and serious nature of ATV crashes. 10,11,15 One report showed that pediatric ATV-related traumas were associated with more interhospital transfers and higher injury severity scores than other trauma admissions. 15 …”
Section: Discussion Pediatric Fatalitiesmentioning
confidence: 99%
“…2 The high risk for death and injury among youth is likely attributable to a number of factors, including physical and mental immaturity, lack of training and experience, operating adult-size machines, riding on roadways, not wearing a helmet, and carrying or being a passenger. [3][4][5][6][7][8][9][10][11][12] According to the Consumer Product Safety Commission (CPSC), youth ,16 years of age have represented approximately one-quarter of all deaths and one-third of all US ATV-related injuries. 13 More than 40% of these pediatric deaths were children ,12 years of age.…”
mentioning
confidence: 99%
“…Given the increased injuries in this age group, as well as data showing more than half of pediatric injuries had occurred on private land, advocacy efforts in our state were successful in further regulating this vulnerable population. 6,39,40 Figure 2 shows that the decline in injuries observed before 2010 was followed by an abrupt 28% drop in the populationbased rate after the absolute age restriction (<14 years old). Specifically, we saw a 50% reduction in injuries in the 10-to 13-year-old age group, suggesting that these strict guidelines contributed to the effects seen.…”
Section: Discussionmentioning
confidence: 99%
“…There is ongoing discussion about what restrictions to include in state laws to best protect young riders. 6,18,26 Debate on the impact of education and training on injury and fatality rates is longstanding. Most ATV riders report having had minimal formal instruction in safe-riding practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation